2013
DOI: 10.1111/eje.12024
|View full text |Cite
|
Sign up to set email alerts
|

Using e‐learning to train dentists in the development of standardised oral health promotion interventions for persons with disability

Abstract: The results indicate that the online training course helped participants to increase self-efficacy and to provide interventions in institutions. This study could have implications for both undergraduate and postgraduate dental education in France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Two studies reported only the length of time students spent on certain e-learning activities such as e-learning animations [24] and game-based platforms [25] However, 10 studies used both the number of connections and length of time spent on the elearning activity by students [12,[26][27][28][29][30][31][32][33][34] (e.g. number of connections to the e-platform and the accumulative time spent completing the online modules [26], or connections and time on pages…”
Section: Figure 1 Flowchart Of Search Processmentioning
confidence: 99%
See 4 more Smart Citations
“…Two studies reported only the length of time students spent on certain e-learning activities such as e-learning animations [24] and game-based platforms [25] However, 10 studies used both the number of connections and length of time spent on the elearning activity by students [12,[26][27][28][29][30][31][32][33][34] (e.g. number of connections to the e-platform and the accumulative time spent completing the online modules [26], or connections and time on pages…”
Section: Figure 1 Flowchart Of Search Processmentioning
confidence: 99%
“…number of connections to the e-platform and the accumulative time spent completing the online modules [26], or connections and time on pages…”
Section: Figure 1 Flowchart Of Search Processmentioning
confidence: 99%
See 3 more Smart Citations